Migration and Racialization in Times of “Crisis”: The Making of Crises and their Effects - Benhadjoudja, Leila; Clark-Kazak, Christina; Garneau, Stéphanie (Université d'Ottawa | University of Ottawa, 2025)
The health crisis, the migration crisis, the humanitarian crisis, and the climate crisis. The repeating reference to the idea of crisis to label numerous social upheavals suggests that we now live in a world defined by crisis. Yet the urgency inherent in a crisis often leads to the normalization of rights violations and increased surveillance, profiling and arbitrary arrests, making visible the state’s control over bodies, and certain bodies, in particular. Migration and Racialization in Times of “Crisis” explores the colonial, racist and sexist underpinnings of various declarations of crisis, as well as their effects. Taken together, these contributions show that the state of crisis manifests as a condition for the maintenance of racial and patriarchal capitalism. The English and French version of this title, though distinct, complement each other to offer a more comprehensive and critical look at this approach of “governing through crisis”.
GENERAL INTRODUCTION Leila Benhadjoudja, Christina Clark-Kazak and Stéphanie Garneau 1. How to define a crisis? Looking back at a concept 2. Thinking about "crises" through the lens of racial capitalism 3. Ways of thinking about crises and migrant, Black, indigenous and racialized populations 4. Overview of the English volume 5. Overview of the French volume THE THEORETICAL AND PRACTICAL POTENTIAL OF ‘ACOMPAÑAMIENTO’ FOR RESEARCH WITH PEOPLE MARGINALISED THROUGH IMMIGRATION CONTROLS Valentina Glockner, Walter Flores, Elaine Chase, Jennifer Allsopp, Ian Warwick, Deborah Zion, Brad Blitz, Ricardo Muniz-Trejo, Penelope Van Tuyl and Theresa Cheng 1. Purpose of the paper 2. Migration, deportations and marginalisation in Central America 2.1. Understanding acompañamiento 2.2. Bringing acompañamiento to research 3. Positionality and motivation 3.1. Relationship of acompañamiento to particular research approaches 4. The ethics of acompañamiento 4.1. Implications for co-creating knowledge 4.2. Concluding thoughts VIVE LA FRANCE! EXALTING FRENCH NATIONALISM THROUGH NEWS MEDIA NARRATIVES OF CALAIS MIGRANTS Maritza Felices-Luna 1. The politics of (in)visibility: foregrounding and erasing migrants in Calais 2. News media narratives of migrant ‘crises’ 3. Walking away from crisis as intelligibility towards crisis as constitutive through narrative analysis 4. Unpacking the figured worlds 4.1. French solidarity 4.2. France under attack 4.3. The points where both figured worlds meet 5. The French national as custodian of French values and guardian of French sovereignty THE VENEZUELAN “MIGRATORY CRISIS” IN THE ECUADORIAN CONTEXT: PROBLEMATIZING IMMIGRANTS AS VICTIMS AND THREATS Martha Alexandra Vargas Aguirre 1. Methodology 2. Context 3. Managing Venezuelan immigration as a crisis 4. Conclusion TOP MANTA: BARCELONA’S UNIONIZED MANTEROS IN THEIR STRUGGLE FOR RECOGNITION AND REDISTRIBUTION Tatiana Llaguno and Marina Gomá 1. Context 2. My dream was not to become a mantero: I am a fisherman 3. El cayuco: Resisting necropolitical deathscapes 4. Weaving networks of solidarity: Re-shaping the city and reframing political belonging 5. Conclusion 6. Acknowledgements COVID-19 IN MONTREAL: SYSTEMIC IMPACT ON PRECARIOUS IM/MIGRANT WORKERS AND THEIR ORGANIZING RESPONSES Manuel Salamanca Cardona 1. Setting the framework for the crisis in Montreal 2. Experiencing the crisis in terms of work, barriers to social protection, and migratory status 3. Highlighting systemic effects of the pandemic, auto-organizing and questioning the State exclusion 4. Self-organizing, critics and co-existence with the State and its institutions in times of pandemic 5. Conclusion ‘DESIGNER MIGRANT’ OR ‘BACKDOOR MIGRANT’: CHALLENGES OF INTERNATIONAL STUDENT IDENTITY IN CANADA Tahseen Chowdhury and Chiedza Pasipanodya 1. Methodology 2. Context 3. Discussion 3.1. Colonial Grammar and the Myths of Western Supremacy 3.2. The Manufactured Crisis of Scarcity, Competition, and Fraud 3.3. The Business and Branding of International Education 3.4. The Grammar of Internationalization 3.5. Student, Migrant, or Worker? Crisis by Design 4. Conclusion
Keywords: Migration Policy; Government by Crisis; Grammar of crisis; Racism; Anti-Racism; Migrants; Refugees; Public Health; Social Justice; Sexism; Capitalism; Nationalism; Populism